2023
DOI: 10.4018/ijskd.334555
|View full text |Cite
|
Sign up to set email alerts
|

Role of HRM Practices in Organization Performance

Lawrence Arokiasamy,
Takemi Fujikawa,
Shishi Kumar Piaralal
et al.

Abstract: In recent years, HRM has received a lot of traction. Human resource management is essential for all types of enterprises. The bulk of research indicates that HRM and organizational performance have a positive link. Each organization's main goal is to attain high levels of performance in its goals and objectives. In this paper, HRM and practices were investigated. What part do human resources play in achieving organizational objectives? This survey will also evaluate HRM practices by analyzing the 40 papers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In recent years, human resource management has received much traction. Companies need to have well-trained human resources to compete successfully (Arokiasamy et al, 2023;Sivathanu & Pillai, 2019).…”
Section: Skills Developmentmentioning
confidence: 99%
“…In recent years, human resource management has received much traction. Companies need to have well-trained human resources to compete successfully (Arokiasamy et al, 2023;Sivathanu & Pillai, 2019).…”
Section: Skills Developmentmentioning
confidence: 99%
“…It is also closely related to the need to concentrate on quality assurance and improvement, which was historically the domain of a select few highly esteemed universities on a global scale. Quality assurance in these institutions is a recent entry adopted by the developed countries to then reach the third world countries due to globalization and the openness of universities to global competition to keep pace with technological development and progress, and thus keep pace with advanced and distinguished universities (Arokiasamy et al, 2024;Casado et al, 2022;Al-Shboul et al, 2017).…”
mentioning
confidence: 99%
“…In recent years, many primary and secondary schools have paid more and more attention to the design and evaluation of students' homework, in order to reduce students' learning burden and improve learning efficiency (Arokiasamy et al, 2024). However, through classroom observation, it can be found that the current homework is biased toward universality and the evaluation method is relatively simple, which cannot fundamentally cultivate students' problem-solving abilities and ultimately only increases the burden on teachers and students (Liu, 2023).…”
mentioning
confidence: 99%